J. M. Coetzee, the Craftsman - Veres, Ottilia (Hungarian Journal of English and American Studies, 2021)
Book review:Attwell, David. J. M. Coetzee and the Life of Writing: Face-to-Face with Time. New York: Viking, 2015. xxiii + 248 pages. ISBN 978-0-525-42961-6. Pbk. $27.95.